Differential expression of bone morphogenetic protein 5 in human lung squamous cell carcinoma and adenocarcinoma. (20th May 2015) - Deng, Taoran; Lin, Dandan; Zhang, Man; Zhao, Qingchuan; Li, Weina; Zhong, Bo; Deng, Yu; Fu, Xiangning
Abstract: Bone morphogenetic proteins (BMPs) play important roles in tumor cell proliferation, metastasis, and invasion. However, the expression patterns of BMPs in patients with non-small-cell lung cancer (NSCLC) and their correlations with NSCLC pathogenesis have not been examined yet. In this study, the mRNA levels of BMP family members in NSCLC tissues were analyzed and results showed that the mRNA levels of BMP5 and BMP7 were significantly down-regulated and up-regulated, respectively, in tumor tissues compared with those in the corresponding noncancerous tissues. Interestingly, the mRNA level of BMP5 was significantly higher in lung adenocarcinoma tissues than that in lung squamous cell carcinoma tissues. Furthermore, results from immunohistochemistry analysis confirmed stronger expression of BMP5 protein in lung adenocarcinoma than in lung squamous cell carcinoma. Our findings suggested that BMP5 might be a potential prognostic biomarker or therapeutic target for patients with NSCLC.